E-Diagnostic Early Detection of Pulmonary Tuberculosis Disease Using Certainty Factor Method - Dina Aulia Arsyika; Firahmi Rizky; Hevlie Winda Nazry S; Amin Harahap (International Journal of Health Engineering and Technology, 2025)
Currently, technological developments are very rapid, this development has brought significant changes to the role and function of computer technology. Pulmonary Tuberculosis Pelnylakit is an infectious disease caused by the infectious bacterium Mylcobactelrium Tubelculosis. The Mellati Community Health Center is one of the Mellati Community Health Centers which provides early detection services for pulmonary tuberculosis patients in the Pelrbaungan District. Pulmonary Tuberculosis disease at the Melati Community Health Center is limited to four with sixteen symptoms. The programming language that will be used is MySQL database and PHP. With this research, the aim is to create a system with accurate results for pulmonary tuberculosis. This expert system uses the certainty factor method and can be used to solve problems regarding pulmonary tuberculosis in patients well. The final result of the diagnosis is in the form of several questions that will be answered by the patient according to the condition they feel.